A New Index of Housing Sentiment - Bork, Lasse; Møller, Stig V.; Pedersen, Thomas Q. (Management Science, 2020)
We propose a new measure for housing sentiment and show that it accurately tracks expectations of future house price growth rates. We construct the housing sentiment index using partial least squares on household survey responses to questions about buying conditions for houses. We find that housing sentiment explains a large share of the time variation in house prices during both boom and bust cycles, and it strongly outperforms several macroeconomic variables typically used to forecast house prices. This paper was accepted by Tyler Shumway, finance.